The Impact of Early Marriage on Social Life in Wakan Village, Jerowaru District, East Lombok Regency - Yuandari, Enti Purnika; Nasuhi, M.; Anggriani, Reni; Maydasari, Elita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The aim of this research is to determine the impact of early marriage on the social life of the community in Wakan Village, Jerowaru subdistrict, East Lombok district. The type of research, used is qualitative research, namely describing existing phenomena through a scientific approach. The data collection techniques used by researchers are observation methods, interview methods and documentation methods. Based on the results of research in Wakan Village, Jerowaru subdistrict, Easy Lombok Regency, the background to early marriage is 1) The relationship between the economic situation of parents and their interest in pursuing education, 2) The tradition of early marriage, 3) The influence of media developments, 4) People’s desires. Parents to merry off their children and, 5) The rise of promiscuity among teenagers. While the impact on social life is 1) Increasing dropout rates, 2) Dissatisfaction in adolescence which leads to extramarital affairs, 3) Lack of emotional maturity which leads to divorce, 4) Occurrence of domestic violence (KDRT).